Flora of Ceará: Siparunaceae - Gustavo Rebechi Brunassi; Elton John de Lírio (Rodriguésia)
Abstract The present work deals with the family Siparunaceae in the state of Ceará, Brazil. The family comprises 53 species in two genera, Siparuna of Neotropical distribution and Glossocalyx (monotypic) occurring in Western Africa. In Brazil, Siparunaceae is represented by the genus Siparuna with 20 species, with the Amazon as its center of diversity with 19 species, followed by the Atlantic Forest with seven species, and Cerrado with six. In Ceará, two species are mentioned in the Flora of Brazil 2020, namely, Siparuna guianensis and Siparuna reginae. This work was based on the examination of physical and virtual herbarium material, types, and bibliographies. Two species of Siparuna were recorded for the state of Ceará, S. guianensis and S. brasiliensis, the second being a new occurrence for the state. A geographic distribution map of the species, an identification key, photographs, taxonomic descriptions, and taxonomic comments are provided.